2017
DOI: 10.1089/scd.2017.0099
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M and TNF-α Induce Alpha-1 Antitrypsin Production in Undifferentiated Adipose Stromal Cells

Abstract: Alpha-1 antitrypsin (A1AT), a circulating acute-phase reactant antiprotease, is produced and secreted by cells of endodermal epithelial origin, primarily hepatocytes, and by immune cells. Deficiency of A1AT is associated with increased risk of excessive lung inflammation and injury, especially following chronic cigarette smoke (CS) exposure. Exogenous administration of mesenchymal progenitor cells, including adipose tissue-derived stromal/stem cells (ASC), alleviates CS-induced lung injury through paracrine ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…48 In the era of regenerative medicine, we and others have shown that the adipose-derived mesenchymal stem cell (MSC)secretome contains AAT with high anti-elastase in vitro activity and other proteins involved in protease/anti-protease balance. 49,50 These findings position allogenic MSC as a novel therapeutic option for AATD patients.…”
Section: Novel Therapiesmentioning
confidence: 92%
“…48 In the era of regenerative medicine, we and others have shown that the adipose-derived mesenchymal stem cell (MSC)secretome contains AAT with high anti-elastase in vitro activity and other proteins involved in protease/anti-protease balance. 49,50 These findings position allogenic MSC as a novel therapeutic option for AATD patients.…”
Section: Novel Therapiesmentioning
confidence: 92%
“…GR signaling in response to GC leads to both anti-inflammatory effects and immune suppression. A known connection between AAT and GR is that GR activation by GC increases AAT production at the transcriptional level (Kadiyala et al , 2016; Ni et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…9 Alpha-1-antitrypsin (A1AT) belongs to the serpin superfamily of proteins and is produced and secreted by cells of endodermal epithelial origin, primarily hepatocytes, and immune cells. It plays important roles in many diseases such as liver disease, emphysema, polyangiitis, and lung diseases [10][11][12][13][14][15] as an anti-protease, anti-inflammatory, and anti-apoptotic agent. 16 Recent studies indicate that A1AT is a key factor in epithelial-to-mesenchymal transition (EMT) in lung cancer.…”
Section: Introductionmentioning
confidence: 99%